Description of probiotic use in preterm infants in England and Wales 2016–2022 - Shalini Ojha; Alex Bottle; Lisa Szatkowski; Cheryl Battersby; Paul Fleming; Janet Berrington; Kate Costeloe; Alice Aveline (BMJ Paediatrics Open)
Objective To describe the use of probiotics among preterm infants in neonatal units and explore factors that influence exposure.Design Observational study using prospectively recorded health data.Setting England and Wales.Patients 48 048 infants born at <32 weeks gestational age (GA) and admitted to a neonatal unit between 1 January 2016 and 31 December 2022.Main outcome measures Measures of probiotic use (number and proportion of infants exposed to probiotics, postnatal age of first probiotic exposure and discontinuation).Results The proportion of infants who received probiotics increased from 9% to 54% over the study period. Median GA of infants given probiotics was 29+3 weeks (IQR 27+3–30+6). Probiotics were started on median day 5 (IQR 2–8), earlier for those born at >28 weeks GA (median day 4, IQR 2–7), most frequently after enteral feeds (66% of exposed infants) and were usually discontinued between 32 and 36 weeks postmenstrual age (PMA) (47% at 32+0–33+6 weeks PMA, 33% at 34+0–35+6 weeks PMA). Among infants cared for in probiotic neonatal intensive care units (defined as units where 50% or more infants born <32 weeks gestation were exposed to probiotics), 23% were never given probiotics. Infants from whom probiotics were withheld had a lower gestational age, lower birth weight z score and higher illness severity score or were more mature.Conclusions By 2022, over half of infants born at <32 weeks GA were exposed to probiotics, but almost one quarter did not receive them despite being in a probiotic unit. Our findings help inform the interpretation of observational data and the design of future studies addressing the continued uncertainty around the safety and efficacy of probiotics.